STRATEGI PENGAJARAN ALAT MUSIK ANGKLUNG DI SMAN 8 CIREBON - Jaja, Suramiharja; Clemy Ikasari Ichwan; Didin Supriadi (Program Studi Pendidikan Musik, 2025)
This research is motivated to find out and describe how Angklung musical instrument teaching strategy at SMAN 8 Cirebon. The research method used is a qualitative research method with a descriptive qualitative approach. The research was conducted at SMAN 8 Cirebon, Cirebon City, West Java. The object of this study is angklung musical instrument teaching strategy at SMAN 8 Cirebon. The data contained is the result of literature studies, interviews, observations, and documentation. The result of this study is that angklung musical instrument teaching strategy at SMAN 8 Cirebon is divided into 3 stages of teaching, namely the basic teaching stage, the advanced teaching stage and the preparation stage for the competition. There are five main components in teaching, namely the existence of objectives, content / material, methods, media, and teaching evaluation. The teaching methods used are lectures, demonstration, imitation and drill. The training process of the Angklung D'Symba Team is carried out regularly once a week, held on Thursdays when returning home from school. However, if the material is prepared for performances and competitions, training is carried out 1 week 2 times on Mondays and Thursdays. If it is close to the appearance time, then exercises can be carried out regularly in a week with a period of 3 months of exercises that are carried out when returning home from school and dispensation during learning hours.